GROWTH OF Caulerpa sp. CULTIVATED WITH THE LONGLINE METHOD IN ROMPO VILLAGE, LANGGUDU DISTRICT, BIMA REGENCY - Rahmawanti, Sinta; Cokrowati, Nunik; Junaidi, Muhammad (Jurnal Media Akuakultur Indonesia, 2021)
Macroalgae that exist in Indonesia and have the potential to be cultivated apart from the Glacilaria sp. and Eucheuma sp. is a type of seaweed Caulerpa sp. The aim of this research was to determine the effect of different planting distances and depths on the growth and antioxidants of Caulerpa sp. which is cultivated using the longline method. The research was carried out in the waters of Rompo Village, Langgudu District, Bima Regency, West Nusa Tenggara. The research method was a factorial Completely Randomized Design (CRD) with two factors. The first factor is the planting distance consisting of 3 treatments. The second factor is depth consisting of 2 treatments. The combination of distance and depth in this study is; A: plant distance 20 cm - 50 cm depth, B: plant distance 30 cm - 50 cm depth, C: plant distance 40 cm - 50 cm depth, D: plant distance 20 cm - 100 cm depth, E: plant distance 30 cm - depth 100 cm and F: planting distance 40 cm - depth 100 cm. The results showed that different planting distances had a significant influence at the 5% level on the growth of Caulerpa sp. and there is no interaction between the JT factor (Planting Distance) and the KD Factor (Depth) on the absolute growth rate of Caulerpa sp. Absolute growth rate of Caulerpa sp. The best treatment was obtained from a planting distance of 30 cm with a depth of 50 cm, namely 111 Â± 27 grams with a specific growth rate of 2,477 Â± 412b %/day. The highest antioxidant content was obtained at a planting distance of 40 cm with a depth of 50 cm, amounting to 45.57%. The conclusion of this research is that the interaction between the planting distance factor and the depth factor has no effect on the absolute growth and specific growth of Caulerpa sp. Different depths have a significant influence on the antioxidant content of Caulerpa sp.